Factorise :-
i) 36( x + y)² - 49( x - y)²
Answers
Answered by
0
Answer:
it's answer is 1105x^2-2210xy+3697y^2
Step-by-step explanation:
step 1. (36X+36y)^2-(49x-49y)^2
step 2. 1296x^2+2592xy+1296y^2-2401x^2-4802xy+2401y^2
step 3. 1296x^2-2401x^2+2592xy-4802xy+1296y^2+2401y^2
step 4. 1105x^2-2210xy+3697y^2 ✓✓✓ answer
Answered by
0
Answer:
( x - 13y) ( -13x +y)
Step-by-step explanation:
36 ( x² + y² + 2xy) - 49 ( x² + y ² - 2xy )
= 36 x² + 36 y² + 72xy - 49 x² - 49 y² + 98 xy
= 36x² - 49x² + 36y² - 49y² + 72xy + 98xy
= -13x²-13y² + 170 xy
= - 13 x² + 170 xy - 13y²
= -13x² + 169xy + 1xy - 13y²
= -13x ( x- 13y) + 1 y ( x - 13y)
= ( x - 13y) ( -13x +y)
So the factors are ( x - 13y) ( -13x +y)
Similar questions
Biology,
4 months ago
Social Sciences,
4 months ago
Math,
4 months ago
Math,
9 months ago
Social Sciences,
9 months ago
Math,
1 year ago